Entrepreneurial Intention of Medical Students in Malaysia: Does Socio-Demographic Profile Matter? - Ashok Kumar, Kavitha; Azam, S.M. Ferdous; Jeppu, Ashok Kumar (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Though there are abundant studies on entrepreneurial intention among students pursuing higher education, there is a lacuna in understanding the entrepreneurial intention of medical students. In the present scenario of increasing unemployment among young medical graduates, this quantitative study was conducted with an aim to examine the level of entrepreneurial intention among medical students and the socio-demographic factors influencing it. Methods: The participants were 318 medical students of a private university in Malaysia. A cross-sectional study design with a validated adapted questionnaire was used to collect data. The data was analysed using descriptive and inferential statistics. Results: A moderately high level of entrepreneurial intention was found among the study population. Regression analysis revealed a statistically significant impact of gender and marital status on their entrepreneurial intention while ethnicity, year of study, household income or educational loan did not have a significant influence. Conclusion: Medical students in Malaysia showed a moderately high inclination towards an entrepreneurial career. Non-economic factors like gender and marital status proved to be stronger influencers of entrepreneurial intention than economic factors. This may help policy makers plan strategies to sustain their entrepreneurial intentions and facilitate for more entrepreneurial activities among young doctors in the future. References: Suciu N, Mărginean C, Meliț L, Ghiga D, Cojocaru C, Popa C. Medical Students’ Personalities: A Critical Factor for Doctor-Patient Communication. International Journal of Environmental Research and Public Health. 2021. 9201;18:9201. Ping S, C, Jing S, R, Yan W, L. Improving the Quality of Medical Education in Malaysia. 2021. February;:13. Wong RY, Kadir SA. Medical education in Malaysia: quality versus quantity. Perspectives on Medical Education. 2017;6:10-1. Li G, Mathematics G, Of S, U. Role of Innovation and Entrepreneurship Education in Improving Employability of Medical University Students. EURASIA Journal of Mathematics, Science and Technology Education. 2017. 2020 Jul 20. 9346;13:27-S28. Bryant P. Self-regulation and entrepreneurial career choice. Regional Entrepreneurship Research Exchange. 2006. 2006;. Karimi S, Biemans HA, Lans T, Mulder M, Chizari M. The Role of Entrepreneurship Education in Developing Students’ Entrepreneurial Intentions. SSRN Electronic Journal. 2012. September;. Liñán F, Fayolle A. A systematic literature review on entrepreneurial intentions: citation, thematic analyses, and research agenda. International Entrepreneurship and Management Journal. 2015;11:907-33. Ajzen I. The theory of planned behavior. Organizational Behavior and Human Decision Processes. 1991;50:179-211. Nagarathana R, Buang N. The Relationship between Attitude, Intention, and Entrepreneurship Career Choice among Malaysian Indian Undergraduates. Akademika. 2016;86. Bandura A. Social foundations of thought and action. 1986;1986. Wu J, Wu L. Evaluation of Medical College Students’ Entrepreneurial Skills and Its Relationship with Social Intelligence. Open J Soc Sci. 2019. 2020 Jul 20;07:13-23. Gurukkal R. Will COVID 19 Turn Higher Education into Another Mode?. Higher Education for the Future. 2020;7:89-96. Fayolle A. Personal views on the future of entrepreneurship education. Entrepreneurship & Regional Development. 2018;25:692-701. Trivedi R. Does university play significant role in shaping entrepreneurial intention? A cross-country comparative analysis. Journal of Small Business and Enterprise Development. 2016;23:790-811. Baliyan S, Baliyan P. Socio-economic Factors as Predictors of Undergraduate Students’ Attitude towards Entrepreneurship in Botswana. Journal of Entrepreneurship and Business Innovation.5:43. Lose T, Kwahene F. Demographical variables and entrepreneurial disposition: a narrative overview of literature. 2021. 32,41;. Gray E, D, De G. Introduction: Real life research: The inside story. Doing Real World Research in Sports Studies. 2013;:21-30. Krejcie R, Morgan D. Determining Sample Size for Research Activities. Educational and Psychological Measurement. 1970;30:607-10. Isreal G. Determining sample size. Sept. 1992. 2009;23. Liñán F, Chen Y. Development and crosscultural application of a specific instrument to measure entrepreneurial intentions. Entrep theory Pract. 2009;33:593-617. Sekaran U, Bougie R. Research methods for business: A skill building approach. Long Range Planning. 2019;26:136. Norasmah O, Othman N. Keberkesanan program keusahawanan remaja di sekolah menengah. 2002;. Peterman N, Kennedy J. Enterprise education: Influencing students’ perceptions of entrepreneurship. Entrep theory Pract. 2003;28:129-44. Kim S, Ahn T, Fouad N. Family Influence on Korean Students’ Career Decisions. Journal of Career Assessment. 2016 Aug;24:513-26. Mwangi P, Mwangi P, Janssen F. Gender, Sexuality, and the Postcolonial Novel. The Cambridge Companion to the Postcolonial Novel. 2014;:116-32. Brady C, Zarb M. Medical students opinions on the inclusion of non-traditional skills in the curriculum. J Entrep Educ. 2018. 2020 Jul 20;21. Sulaiman NC, Akhir NM, Hussain N, Jamin R, Ramli N. Data on the impact of socioeconomic status on academic achievement among students in Malaysian public universities. Data in Brief. 2020;31:106018. Department of Statitics Malaysia. <a href="http://172.16.243.210/index.php/mjmhs/texture/1.%20https://www.dosm.gov.my/%20v1/index.php?r=column/cthemeByCat&cat%20%20=124&bul_id=bHY0SXAyVWFzeFNodDQy%20WFBKL2U0dz09&menu_id=Tm8zcnRjdVRNWWlpWjRlbmtlaDk1UT09" target="_blank" rel="noopener">1. https://www.dosm.gov.my/ v1/index.php?r=column/cthemeByCat&cat=124&bul_id=bHY0SXAyVWFzeFNodDQyWFBKL2U0dz09&menu_id=Tm8zcnRjdVRNWWlpWjRlbmtlaDk1UT09 Nguyen A, Do TH, Vu TT, Dang K, Nguyen H. Factors affecting entrepreneurial intentions among youths in Vietnam. Children and Youth Services Review. 2019;99:186-93. Pihie ZL, Akmaliah Z. Entrepreneurship as a Career Choice : An Analysis of Entrepreneurial Self-Efficacy and Intention of University Students. Eur J Soc Sci. 2009. March;9:338-49. Kerr S, Kerr W, Xu T. Personality Traits of Entrepreneurs: A Review of Recent Literature. Foundations and Trends® in Entrepreneurship. 2018;14:279-356. Amiry H, Alibeigi A, Ghassempouri H. Identify the Attitudes of Agricultural Postgraduate Students towards Motivations on Entrepreneurial Actions from the Viewpoint of Three Universities of (Razi, Bu-Ali-Sina and Ramin) in Iran. Dev Ctry Stud. 2015;5:80-4. Bauman A, Lucy C. Enhancing entrepreneurial education: Developing competencies for success. The International Journal of Management Education. 2021;19:100293. Devi A, Ghazi H, Ariffin I, Yajid M. Level of Entrepreneurship Competence and Readiness Among Medical Students in A Private University in Shah Alam, Malaysia. Journal of Entrepreneurship and Business. 2020;8. Haus I, Steinmetz H, Isidor R, Kabst R. Gender effects on entrepreneurial intention: a meta‐analytical structural equation model. International Journal of Gender and Entrepreneurship. 2013;5:130-56. Israr M, Saleem M. Entrepreneurial intentions among university students in Italy. Journal of Global Entrepreneurship Research. 2018;8:1-14.